Articulation of postsurgical patient discharges: coordinating care transitions from hospital to home. (17th June 2022) - Abraham, Joanna; Kandasamy, Madhumitha; Huggins, Ashley
Abstract: Background: Cardiac surgery patients are at high risk for readmissions after hospital discharge- few of these readmissions are preventable by mitigating barriers underlying discharge care transitions. An in-depth evaluation of the nuances underpinning the discharge process and the use of tools to support the process, along with insights on patient and clinician experiences, can inform the design of evidence-based strategies to reduce preventable readmissions. Objective: The study objectives are 3-fold: elucidate perceived factors affecting the postsurgical discharge care transitions of cardiac surgery patients going home; highlight differences among clinician and patient perceptions of the postsurgical discharge experiences, and ascertain the impact of these transitions on patient recovery at home. Methods: We conducted a prospective multi-stakeholder study using mixed methods, including general observations, patient shadowing, chart reviews, clinician interviews, and follow-up telephone patient and caregiver surveys/interviews. We followed thematic and content analyses. Findings: Participants included 49 patients, 6 caregivers, and 27 clinicians. We identified interdependencies between the predischarge preparation, discharge education, and postdischarge follow-up care phases that must be coordinated for effective discharge care transitions. We identified several factors that could lead to fragmented discharges, including limited preoperative preparation, ill-defined discharge education, and postoperative plans. To address these, clinicians often performed behind-the-scenes work, including offering informal preoperative preparation, tailoring discharge education, and personalizing postdischarge follow-up plans. As a result, majority of patients reported high satisfaction with care transitions and their positive impact on their home recovery. Discussion and conclusions: Articulation work by clinicians (ie, behind the scenes work) is critical for ensuring safety, care continuity, and overall patient experience during care transitions. We discuss key evidence-based considerations for re-engineering postsurgical discharge workflows and re-designing discharge interventions.